Factors associated with knowledge of p-value in a sample of medical students - Vera-Ponce, Víctor Juan; Torres-Malca, Jenny Raquel; Zuzunaga Montoya, Fiorella Elvira; De la Cruz- Vargas, Jhony A.; Cruz-Ausejo, Liliana (Medicina Clínica y Social, 2022)
ABSTRACTIntroduction: The role of p-value knowledge for clinical practice is elemental; however, insufficient evidence on this is found in health science students.Objective: To determine the factors associated with p-value knowledge in human medical students.Methods: Analytical cross-sectional study. Application of a virtual survey to human medicine students from different faculties in Peru.Results: 54.69% had sufficient knowledge of p-value. The multivariate analysis found a statistically significant association with having sufficient knowledge on this topic in those who were between 6th to 9th semester (APr: 1.118; 95% CI 1.051 - 1.412; p=0.009) and medical internship (APr: 1.234; 95% CI 1.073 - 1.418; p=0.003); taking an external course in biostatistics, epidemiology or research (APr: 1.420; 95% CI 1.227 - 1.643; p
Keywords: knowledge; association; statistical & numerical data; students